Consequences of acute oxidative stress in Leishmania amazonensis: From telomere shortening to the selection of the fittest parasites - da Silva, Marcelo Santos [UNESP]; Segatto, Marcela [UNESP]; Pavani, Raphael Souza; Gutierrez-Rodrigues, Fernanda; Bispo, Vanderson da Silva; de Medeiros, Marisa Helena Gennari; Calado, Rodrigo Tocantins; Elias, Maria Carolina; Cano, Maria Isabel Nogueira [UNESP] (Elsevier, 2017)
Leishmaniasis is a spectrum of diseases caused by parasites of the genus Leishmania that affects millions of people around the world. During infection, the parasites use different strategies to survive the host's defenses, including overcoming exposure to reactive oxidant species (ROS), responsible for causing damage to lipids, proteins and DNA. This damage especially affects telomeres, which frequently results in genome instability, senescence and cell death. Telomeres are the physical ends of the chromosomes composed of repetitive DNA coupled with proteins, whose function is to protect the chromosomes termini and avoid end-fusion and nucleolytic degradation. In this work, we induced acute oxidative stress in promastigote forms of Leishmania amazonensis by treating parasites with 2 mM hydrogen peroxide (H2O2) for 1 h, which was able to increase intracellular ROS levels. In addition, oxidative stress induced DNA damage, as confirmed by 8-oxodGuo quantification and TUNEL assays and the dissociation of LaRPA-1 from the 3′ G-overhang, leading to telomere shortening. Moreover, LaRPA-1 was observed to interact with newly formed C-rich single-stranded telomeric DNA, probably as a consequence of the DNA damage response. Nonetheless, acute oxidative stress caused the death of some of the L. amazonensis population and induced cell cycle arrest at the G2/M phase in survivor parasites, which were able to continue proliferating and replicating DNA and became more resistant to oxidative stress. Taken together, these results suggest that adaptation occurs through the selection of the fittest parasites in terms of repairing oxidative DNA damage at telomeres and maintaining genome stability in a stressful environment.
Keywords: DNA repair; LaRPA-1; Leishmania amazonensis; Oxidative stress; Telomere shortening